Raw X-ray fluorescence (XRF) scanning and grain size analysis of ODP Hole 121-752A at Broken Ridge - Jing Lyu; Gerald Auer; Or M Bialik; Beth A Christensen; Ryo Yamaoka; David De Vleeschouwer (PANGAEA, 2023)
The Ocean Drilling Program (ODP) Site 752 (ODP Expedition 121), located on Broken Ridge in the Indian Ocean, provides a high-quality, continuous sediment archive. Bulk chemical records of Site 752 were measured using X-ray fluorescence core scanning using an Itrax XRF scanner using a Molybdenum X-ray source at the Kochi Core Center, Kochi, Japan. The elemental composition of the sediment was reported as counts. We use XRF data to reconstruct an eccentricity-tuned age-depth model. Grain size measurements of 123 samples throughout the last 23 million years from the same core were conducted in the Particle-Size Laboratory at MARUM, University of Bremen with a Beckman Coulter Laser Diffraction Particle Size Analyzer LS 13320. The particle-size distribution result of a sample consists of 116 size classes (from 0.04 to 2000 μm). The high-resolution XRF data set (N = 3118) and the result of grain size analysis can be used to construct paleoceanographic changes in the Indian Ocean since 23 Ma. These results provide new insights into the role of astronomical forcing in shaping the Indian Ocean extquotesingles dynamics and highlight the potential of ODP Site 752 as a valuable resource for future paleoceanographic research.